MEASURING THE EXPORT POTENTIAL OF TOBACCO INDUSTRY AND INDONESIAN TOBBACO PRODUCTS - Eman Sulaeman Nasim; Jajang Gunawijaya (Universitas Mercu Buana, 2021)
Smoking is one of activities that is deeply rooted in Indonesian culture so that the economic contribution from this actvities is quite significant in the Indonesian economy. Along with the development of various policy discourses that counter the development of the tobacco industry and processed tobacco products, such as an increase in excise rates for tobacco (CHT) also there is shock of pandemic situation, the sustainability of local tobacco industry needs to be a concern and also has to be prompted the urgency to expand the market to another countries through export activities. This research aims to measure the impact of the potential utilization of tobacco and processed tobacco commodity export activities by considering production capacity, available policy frameworks, and challenges that faced by industrial actors. By using quantitative approach through the calculation of Input-Output Tables, as well in-depth literature studies on the eport regulatory framework in Indonesia and in other countries also related studies on the opportunities and challenges of tobacco commodity exporters,this research succeeded in providing several findings. By considering the scale of production and eksport opportunities in trade balance deficit countries for tobacco commodities and their derivative products, the measured export potential is in the range of 17.5 bilion – 34.9 bilion USD, which 17.5 bilion USD if Indonesia export to countries with trade deficit ba;ance which has income per capita lower than Indonesia and 34.9 bilion USD when Indonesia is able to export to 20 major countries with the largest trade deficit balance. Policies that need to be taken to archieve this potential include uniformity of commodity quality standarts with international standards, encouraging production incentive policies through subsidy scheme and capital goods grants, and reducing export duties on several suppoting components of tobacco production and its derivatives.